Integrative Therapy for Smile Lines: An Experimental Study of the Combination of Acupuncture and Aloe Vera Gel - Syafira Mahrunnisa, Hanum; Endah Happy Patriyani, Ros; Tri Haryanto, Joko; Aditya Nugrahai, Nurtama (HAKTI : Indonesian Acupuncture Therapists Association, 2025)
The desire to look young is commonly felt by middle-aged women as wrinkles appear, including in the smile line area. The increasing number of elderly people in Sukoharjo has an impact on the prevalence of skin aging problems. Acupuncture and aloe vera gel are known to improve skin elasticity, but there has been no research that combines the two for smile line wrinkles. This study aims to determine the effectiveness of aloe vera gel combination acupuncture therapy on the scale of wrinkles in the smile line. This study used a quantitative research type with a quasy-experimental research design with a two-group pretest posttest design. The sample consisted of 42 research subjects, divided into two groups, namely the acupuncture therapy group combined with aloe vera gel, and the acupuncture therapy group with 21 research subjects each. The results of the Independent T-Test from the data on changes in the scale of wrinkles in the smile line area obtained a p value> 0.05. This means that there is no significant difference in acupuncture therapy combined with aloe vera gel. So it can be concluded that both groups showed changes in the scale of wrinkles in the smile line area. Both groups showed effective results in reducing the scale of wrinkles in the smile line area, but there was no significant difference.